ANALISIS TEKNIK LEMPARAN KE DALAM DENGAN AWALAN UNTUK MENGHASILKAN LEMPARAN TEPAT SASARAN PADA PEMAIN SEPAK BOLA - DWI PRASETYA, TULUS Dwi (Jurnal Kesehatan Olahraga, 2014)
ANALISIS TEKNIK LEMPARAN KE DALAMDENGAN AWALAN UNTUK MENGHASILKAN LEMPARAN TEPAT SASARAN PADA PEMAIN SEPAKBOLA(Studi pada pemain sepakbola Fatahillah 354 Surabaya)Tulus Dwi PrasetyaPendidikan Kesehatan Dan Rekreasi, Fakultas Ilmu Keolahragan UNESAABSTRACTMotion analysis in sport are needed by the coach or expert biomechanical motion to correct the movement. Keep in mind that all human movement can not be separated from the principles of physics, as well as the motion of the throw in. So far, many players who throw in has wrong and ineffective movement in terms of biomechanics. Therefore the research question posed in this study is how the effective motion series of throw in with the prefix in terms of biomechanics?. The purpose of this study is to obtain information and data from a throw in motion analysis with the prefix on football players of Fatahillah 354 Surabaya related to the speed of the ball when out of hand, throw angle, angle elbow / arm, and body position. The type of this research is descriptive research analysis with analysis techniques using the principles of biomechanics and measurement using Dartfish statistical software. The results of the three subjects, who each made three throws, the third thrower made the initial speed of the ball when off the hands is 20.5 m / s with an throw angle approaching the optimum projection angle 45 ° is 40.1 °, the distance of his throw is 23.20 meters, which it closest distance of the farthest distance specified.Keywords : Throw, AnalysisABSTRAK